{Deep structure of the Hellenic lithosphere from teleseismic Rayleigh-wave tomography} - Kassaras, I.; V. Kapetanidis; A. Karakonstantis; Papadimitriou, P. (Geophysical Journal International, 2020)
{This research provides new constraints on the intermediate depth upper-mantle structure of the Hellenic lithosphere using a three-step Rayleigh-wave tomography. Broadband waveforms of about 1000 teleseismic events, recorded by ∼200 permanent broadband stations between 2010 and 2018 were acquired and processed. Through a multichannel cross-correlation technique, the fundamental mode Rayleigh-wave phase-velocity dispersion curves in the period range 30 to 90 s were derived. The phase-velocities were inverted and a 3-D shear velocity model was obtained down to the depth of 140 km. The applied method has provided 3-D constraints on large-scale characteristics of the lithosphere and the upper mantle of the Hellenic region. Highlighted resolved features include the continental and oceanic subducting slabs in the region, the result of convergence between Adria and Africa plates with the Aegean. The boundary between the oceanic and continental subduction is suggested to exist along a trench-perpendicular line that connects NW Peloponnese with N. Euboea, bridging the Hellenic Trench with the North Aegean Trough. No clear evidence for trench-perpendicular vertical slab tearing was resolved along the western part of Hellenic Subduction Zone; however, subcrustal seismicity observed along the inferred continental-oceanic subduction boundary indicates that such an implication should not be excluded. The 3-D shear velocity model supports an N-S vertical slab tear beneath SW Anatolia that justifies deepening, increase of dip and change of dip direction of the Wadati-Benioff Zone. Low velocities found at depths \< 50 km beneath the island and the back-arc, interrelated with recent/remnant volcanism in the Aegean and W. Anatolia, are explained by convection from a shallow asthenosphere.}